La motivación escolar y su influencia en el rendimiento académico de los niños y niñas del séptimo año de Educación General Básica de la Unidad Educativa El Limo del cantón Puyango, provincia de Loja, periodo lectivo 2021 - 2022. Lineamientos alternativos. - Oviedo Ortiz, Lineyda Maricela (2022)
The present research work entitled; school motivation and its influence on the academic performance of boys and girls from the seventh grade of general basic education at El Limo school in Puyango canton, Loja province, during the school year 2021 – 2022. Alternative guidelines. The general objective was to contribute to the improvement of the academic performance of boys and girls through school motivation during the seventh grade of General Basic Education at the El Limo Educational school. The instruments used were: observation cards and a survey addressed to the teacher and students. Those instruments allowed to point out how motivation influences the academic performance in students. The methodology used was descriptive, with a quantitative-qualitative type of study, using different methods like descriptive, analytical, synthetic, inductive, deductive and statistical, which allowed the research process to be carried out. The most relevant results allowed to conclude the main causes of the absence of motivation are personal and academic aspects, which affects the academic performance of boys and girls from the seventh grade of general basic education at El Limo school; those aspects should be taken into account since it is essential that constant school motivation should be part of the teacher in the training of the students. Taking this into consideration, interactive workshops were proposed to improve school motivation in students. Keys words: school motivation, education, academic performance, teaching, learning.